Health-promoting lifestyle behaviours of nursing students of a tertiary care institute - Borle, Pradip S.; Parande, M. A.; Tapare, V. S.; Kamble, Vidya Sanjeev; Bulakh, Pradymunaa C. (International Journal Of Community Medicine And Public Health, 2017)
Background: In addition, Health promoting behaviours among the nursing students may affect the quality of patient education. Therefore, this study was undertaken to determine the health-promoting lifestyle behaviours of nursing students in a tertiary care institute, Maharashtra. Methods: This cross-sectional study was performed on 124 nursing students. Health Promotion Lifestyle Profile Proforma (HPLP)was prepared which consists of two parts, Part I deals with the sociodemographic characteristics of the participants and Part II of the proforma deals with Health-promoting lifestyle information which was a modified version of Health Promoting Lifestyle Profile II (HPLP II). It consists of 46 items divided into 7 subscales (Health responsibility, Physical activity, Food practices, Spiritual growth, Self-concept, Inter personal relations and Stress management). Internal consistency (Cronbach’s alpha) of this tool was 0.8197. Permission of Institute Ethical Committee was taken. Descriptive statistics were used to describe HPLP. Data was analyzed by using analysis of variance (ANOVA) and Mann Whitney test. Results: Majority 89(71.77%) were have good HPLP score and 29(23.39%) were excellent category. The mean overall (Total) HPLP score was 62.27±9.66 (range 33-87). The highest mean score in the subscale were for self-concept and spiritual growth. The lowest scores were for food practices and physical activity. Highly significant difference (p<0.0001) was found between overall mean HPLP scores among the different age groups. Conclusions: These nursing students had reasonably good orientations towards health behaviours. Attention need to be paid for healthier food choices. Health promotion planning to motivate students for regular physical activity with the purpose of promoting health and preventing diseases is necessary.